Audio app using MATLAB app designer (I) - Mohamed Shameer S/O Hajanajmudeen (Nanyang Technological University, 2024)
This report discusses the development of an audio application using MATLAB App Designer to enhance the learning experience of signal processing. Considering signals are abstract concepts, understanding and visualising such concepts are difficult. This developed application serves to link theoretical concepts to a hands-on learning experience. This robust audio application is capable of performing digital filtering to visualize and hear audio signals in both time and frequency domains by manipulating the different parameters, signal amplification and lastly adding noise to signals. These key features provide students with a hands-on learning experience strengthening their learning. In conclusion, the developed audio application provides a beneficial tool for students learning signal processing.